Relación entre composición y densidad de la cubierta vegetal leñosa y las características superficiales del suelo en Bosques Mixtos de Quercus del Sur de la Península Ibérica - GARCÍA, L V; POLO, A; Maltez-Moro, S; Gutiérrez, E; PÉREZ-RAMOS, I M; JORDÁN, A; MARTÍNEZ-ZAVALA, L; MARAÑÓN, T (Tendencias Actuales de la Ciencia del Suelo, 2004)
We studied the relationships between different estimates of the woody canopy density; different estimates of litter release and accumulation, and different soil properties (mainly soil reaction and macronutrient level) which have been recognised as potentially relevant for plant establishment and development in mixed Quercus forest from Natural Park “do Sudoeste Alentejano e Costa Vicentina”, Portugal (with Q. suber, Q. faginea as dominant tree species) and Natural Park “Los Alcornocales”, Spain (with Q. suber and Q. canariensis). We have found 1) A highly significant, quantitative, relationship between litter accumulation and overall canopy density. These relationships can be established either by using objective (but time-consuming) measures (by sampling or using ad hoc measuring devices) or by calibrated by-eye estimates of three simultaneous observers; 2) A significant relationship between some soil properties (N, P, ammonium) and both canopy density and litter accumulation. We conclude that these relationships are interesting in two ways: 1) They may allow to establish ‘ecotransfer functions’ for these forests (i.e. estimates o predictions about surface litter accumulation or surface values for soil properties, as organic carbon, N or P contents, by using quick field estimates of canopy density or even remote sensing estimates of canopy density), after suitable calibrations. 2) Since some soil chemical properties with known ecological relevance (e.g. C, N, P contents, soil reaction) in forest regeneration may change in a close relationship with other more studied, better known, ecological factors (light, moisture, temperature), attention should be paid to separate direct (e.g. light limitation) versus indirect (soil or litter mediated) effects of woody canopy when evaluating ecological responses at the understorey, while studying forest regeneration processes.
Keywords: acumulación de hojarasca; densidad cubierta vegetal leñosa; dosel leñoso; Quercus (voyant); suelo

Relación entre composición y densidad de la cubierta vegetal leñosa y las características superficiales del suelo en Bosques Mixtos de Quercus del Sur de la Península Ibérica - Garcia, L. V.; POLO, A.; Maltez-Moro, S.; GUTIÉRREZ, E.; PÉREZ-RAMOS, I. M.; JORDÁN, A.; MARTÍNEZ-ZAVALA, L.; MARAÑON, T. (Tendencias Actuales de la Ciencia del Suelo, 2004)
We studied the relationships between different estimates of the woody canopy density; different estimates of litter release and accumulation, and different soil properties (mainly soil reaction and macronutrient level) which have been recognised as potentially relevant for plant establishment and development in mixed Quercus forest from Natural Park “do Sudoeste Alentejano e Costa Vicentina”, Portugal (with Q. suber, Q. faginea as dominant tree species) and Natural Park “Los Alcornocales”, Spain (with Q. suber and Q. canariensis). We have found 1) A highly significant, quantitative, relationship between litter accumulation and overall canopy density. These relationships can be established either by using objective (but time-consuming) measures (by sampling or using ad hoc measuring devices) or by calibrated by-eye estimates of three simultaneous observers; 2) A significant relationship between some soil properties (N, P, ammonium) and both canopy density and litter accumulation. We conclude that these relationships are interesting in two ways: 1) They may allow to establish ‘ecotransfer functions’ for these forests (i.e. estimates o predictions about surface litter accumulation or surface values for soil properties, as organic carbon, N or P contents, by using quick field estimates of canopy density or even remote sensing estimates of canopy density), after suitable calibrations. 2) Since some soil chemical properties with known ecological relevance (e.g. C, N, P contents, soil reaction) in forest regeneration may change in a close relationship with other more studied, better known, ecological factors (light, moisture, temperature), attention should be paid to separate direct (e.g. light limitation) versus indirect (soil or litter mediated) effects of woody canopy when evaluating ecological responses at the understorey, while studying forest regeneration processes.
The following values have no corresponding Zotero field: periodical: Tendencias Actuales de la Ciencia del Suelo
Keywords: acumulación de hojarasca; densidad cubierta vegetal leñosa; dosel leñoso; Quercus (voyant); suelo

Caracterización de las poblaciones de Fusarium Link de suelos de dehesas de Badajoz - Rodríguez-Molina, M. C.; TORRES-VILA, L. M.; TELLO MARQUINA, J. C.; BLANCO SANTOS, A.; PALO NÚÑEZ, E. J.; Marquina, J. C. Tello (Boletín de Sanidad Vegetal Plagas, 2001)
La dehesa ocupa en Extremadura una superficie aproximada de 1.800.000 ha y constituye un ecosistema único en el que se combina la producción agro-silvo-pastoraí. Aunque la dehesa está sometida a la acción antrópica, normalmente ésta no provoca la misma perturbación que en las zonas de cultivo agrícola. Sin embargo se desconoce si la micoflora de sus suelos es similar a la de los suelos de áreas no cultivadas o a los de zonas agrícolas. La caracterización de las poblaciones de Fusarium de los suelos de 18 dehesas de Badajoz con arbolado de encina efectuada en este estudio indica que el gé- nero se encuentra ampliamente distribuido en estos suelos. Además de ser detectada su presencia en todos los suelos muestreados, las densidades de población fueron elevadas en general. Las especies aisladas fueron F. oxysporum, F. roseum y F. solani, con un pre- dominio claro de F. oxysporum seguida por F. roseum. Los resultados obtenidos indican que los Fusaria son pobladores naturales de los suelos de dehesa de Badajoz.
Keywords: Dehesa; densidad de población; fusarium; suelo

Estudio ecológico de los pastizales de dehesa en la provincia de Badajoz. Tipificación preliminar de la vegetación empleando el análisis de correspondencias - MARAÑÓN, T; Figueroa, E; Cota, H; Doncel, J L; García Novo, Francisco (Pastos, 1977)
42 grasslands of Badajoz and Huelva provinces (Western Spain) were studied recording plant species frequencies with 10 quadrats (20 X 20 cm.) randomly distributed over 2 X 2 m. plots taken under the crown of Quercus rotundifolia trees. Soil samples collected on every plot were analysed for pH, orgainic matter, P, Ca, K and Na. Frequency matrix (80 plant species X 42 plots) was analysed by the method know as "Analyse des Correspondences" (BENZECRI, 1973). The two main components (accounting for about 20 % of the overall variation) sepárate plots into six recognizable groups (grassland types). A preliminary attempc to interpret those groups is made in terms of biotope (soil and substrate) differencies. The two main directions of variation found correspond to an eutrophization gradient (poor acidic versus rich basic soils) and to an erosión gradient (soil erosión versus pedogenesis). Secondary causes of variation are interpreted as due to lithology, climate and management. Further analysis of present data is currently under way.
Keywords: Dehesa; pastizales; suelo; vegetación (voyant)